2019
DOI: 10.1021/acsanm.9b01174
|View full text |Cite
|
Sign up to set email alerts
|

Air-Stable n-Type Single-Walled Carbon Nanotubes Doped with Benzimidazole Derivatives for Thermoelectric Conversion and Their Air-Stable Mechanism

Abstract: The development of n-type single-walled carbon nanotubes (SWCNTs) stable under an air atmosphere is a key issue to prepare an efficient and stable thermoelectric conversion device using SWCNTs. Doping of SWCNT sheets with 2-(2-methoxyphenyl)-1,3-dimethyl-2,3-dihydro-1H-benzo­[d]­imidazole (o-MeO–DMBI) offers air-stable n-type SWCNT sheets. However, a clear mechanism of the stabilization in air has not been clarified yet. In this study, air stability is found to largely depend on the doping concentration. Adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 60 publications
7
63
0
Order By: Relevance
“…This indicated that the amount of oxygen adsorption was reduced with the number of heat treatments. Therefore, we concluded that this phenomenon occurred because the surfactant was tightly linked with the SWCNTs, which prevented surface oxidation 45,46 . www.nature.com/scientificreports www.nature.com/scientificreports/ Spectroscopic analyses of SWCNT films with surfactants.…”
Section: Stability Of N-type Seebeck Coefficient In Swcnt Films With mentioning
confidence: 94%
See 1 more Smart Citation
“…This indicated that the amount of oxygen adsorption was reduced with the number of heat treatments. Therefore, we concluded that this phenomenon occurred because the surfactant was tightly linked with the SWCNTs, which prevented surface oxidation 45,46 . www.nature.com/scientificreports www.nature.com/scientificreports/ Spectroscopic analyses of SWCNT films with surfactants.…”
Section: Stability Of N-type Seebeck Coefficient In Swcnt Films With mentioning
confidence: 94%
“…As a result, the resulting www.nature.com/scientificreports www.nature.com/scientificreports/ SWCNT film has poor surfactant content. This study did not investigate the amount of surfactant required for n-type doping, but the surfactant content contributed to the stability of the n-type Seebeck coefficient 45 .…”
Section: Stability Of N-type Seebeck Coefficient In Swcnt Films With mentioning
confidence: 99%
“…Finally, to study the superiority of anisotropy control for TE power generation, a single cell structure was fabricated by doping half of the sheet using 2-(2-methoxyphenyl)-1,3-dimethyl-2,3-dihydro-1H-benzo[d]imidazole ( o -MeO-DMBI) [ 13 ] as an n-dopant, and the device was placed on a hot plate ( Figure 6(a )). By setting the temperature of the hot plate to 50°C, the temperature gradient between the middle and the end of the SWCNT-w/o was ca.…”
Section: Resultsmentioning
confidence: 99%
“…Under these circumstances, many researchers have attempted to fabricate SWCNTs with n-type properties using various experimental approaches 26,27,28,29,30 . Nakashima et al prepared air-stable n-type SWCNTs doped with benzimidazole derivatives and discussed their air-stable mechanism 31 . Nonoguchi et al investigated new doping reagents of ordinary salts with crown ethers to create air-and thermally stable n-type SWCNTs 32 .…”
Section: Introductionmentioning
confidence: 99%